Acquiring the user’s opinion by using a generalized Context-aware Recommender System for real-world applications - Venkata Murali Krishna, Chinta; G. Appa Rao, Dr (International Journal of Engineering and Technology, 2018)
Acquiring the user’s opinion on specific things undoubtedly changes according to the given context. A context-aware or Multidimensional Recommender System can adapt its behaviour according to the user’s personal or environmental context. The same user may express or use completely different decision-making ways for various contexts to express the opinion .So, correct anticipation of user need depends upon the amount to which the relevant discourse data is in incorporated within the user’s opinion type. Here, we propose a generalized Context-aware recommender system that is suitable for all applications where a contextual segment plays a major role to find user’s opinion in real-world applications.